Impact of Energy Usage, Economic Growth and Structural Industry Changes on Carbon Emissions in Bangladesh - Gow, Jeff; Saba, Saidatus (International Journal of Energy Economics and Policy, 2024)
This study examines the dynamic relationship between carbon (CO2) emissions and energy usage, economic growth, and the changing industry structure in Bangladesh using annual time series data from 1972 to 2020. To this end, the ARDL Bound co-integration approach as well as the ECM method were employed to analyze the dynamics in the long and short run respectively. The findings reveal a strong positive long-run association between CO2 emissions, economic growth, industry value added and GDP. For agriculture and services value added, no significant long-run relationship could be found. However, both industrial and service sectors show dynamism in the short run indicating that structural industry changes are already reducing CO2 emissions. Thus, the pressing concerns regarding the increase in emissions and the imperative to achieve its growth potential, Bangladesh ought to foster innovative technological, economic, and social solutions that can harmonize energy-intensive development with a heightened emphasis on clean energy adoption, energy conservation initiatives, and efficiency enhancements.